Screen printed 3D microfluidic paper-based and modifier-free electroanalytical device for clozapine sensing - Ghanbari, Mohammad Hossein; Biesalski, Markus; Friedrich, Oliver; Etzold, Bastian (Analyst, 2024)
The increasing demand in healthcare for accessible and cost-effective analytical tools is driving the development of reliable platforms to the customization of therapy according to individual patient drug serum levels, e.g. of anti-psychotics in schizophrenia. A modifier-free microfluidic paper-based electroanalytical device (μPED) holds promise as a portable, sensitive, and affordable solution. While many studies focus on the working electrode catalysts, improvements by engineering aspects e.g. of the electrode arrangement are less reported. In our study, we demonstrate the enhanced capabilities of the 3D electrode layout of μPED compared to 2D μPED arrangements. We especially show that screen printing can be employed to prepare 3D μPEDs. We conducted a comparison of different 2D and 3D electrode arrangements utilizing cyclic voltammetry in [Fe(CN)6]3−/4−, along with square-wave voltammetry for clozapine (CLZ) sensing. Our findings reveal that the utilization of the 3D μPED leads to an increase in both the electrochemically active surface area and the electron transfer rate. Consequently, this enhancement contributes to improve sensitivity in the CLZ sensing. The 3D μPED clearly outperforms the 2D μPED arrangement in terms of signal strength. With the 3D μPED under the optimized conditions, a linear dose-response for a concentration range from 7.0 to 100 μM was achieved. The limit of detection and sensitivity was determined to be 1.47 μM and 1.69 μA μM−1 cm−2, respectively. This evaluation is conducted in the context of detection and determination of CLZ in a human blood serum sample. These findings underscore the potential of the 3D μPED for future applications in pharmacokinetic analyses and clinical tests to personalize the management of schizophrenia.
CRIS-Team Scopus Importer:2024-10-25